2000
DOI: 10.1007/pl00005833
|View full text |Cite
|
Sign up to set email alerts
|

Odontoblast Differentiation of Human Dental Pulp Cells in Explant Cultures

Abstract: In order to elucidate the mechanisms involved in human dentin formation, we developed a cell culture system to promote differentiation of dental pulp cells into odontoblasts. Explants from human teeth were cultured in Eagle's basal medium supplemented with 10% or 15% fetal calf serum, with or without beta-glycerophosphate (beta GP). Addition of beta GP to the culture medium induced odontoblast features in the cultured pulp cells. Cells polarized and some of them exhibited a typical cellular extension. In some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
175
2
16

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(203 citation statements)
references
References 30 publications
10
175
2
16
Order By: Relevance
“…Previous studies have looked at the odontogenic potential of adult human dental pulp by using a number of organ, explant, and cell-culture methods and noted the ability of such cultures to mineralize, at least in part (4,19,20,31). Our data also demonstrates the potential of DPSCs to form calcified deposits in vitro, as do BMSCs (5,6,32).…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have looked at the odontogenic potential of adult human dental pulp by using a number of organ, explant, and cell-culture methods and noted the ability of such cultures to mineralize, at least in part (4,19,20,31). Our data also demonstrates the potential of DPSCs to form calcified deposits in vitro, as do BMSCs (5,6,32).…”
Section: Discussionsupporting
confidence: 61%
“…To study the expression of TLRs by odontoblasts, we used a pure population of cells generated in vitro that are similar in many aspects to in vivo odontoblasts (14,16). We observed the constitutive expression of TLR1-6 and 9 genes but not TLR7, 8, and 10 genes.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used odontoblasts generated in vitro from cultures of human dental pulp explants (14). In these conditions, dental pulp cells give rise to highly differentiated cells that exhibit many odontoblast features such as cell body polarization, formation of a typical process at the cell pole opposite to the nucleus, and strong expression of specific markers, including type I collagen, dentin sialophosphoprotein (DSPP), TGF-␤1, phosphate regulating gene with homologies to endopeptidases on the X chromosome, osteoadherin, and reelin (14,15,16,17).…”
mentioning
confidence: 99%
“…19,20 Easy obtained potential with minimum pain & morbidity make human DPSCs as a valuable source of MSCs compared to the ordinary sources, such as bone marrow mesenchymal stem cells 21 . In general, DPSCs have been isolated by either outgrowth method, i.e., migration of stem cells from pulp tissue explants (DPSC-OG) [22][23][24] , and/or by enzymatic digestion (DPSC-ED) 4,6,25 . Previous studies have shown that the isolation method and culture conditions can induce different populations or lineages under in vitro passages 26,27 .…”
Section: Introductionmentioning
confidence: 99%